THE PERCEPTION OF POPULATIONS UPON CORRUPTION IN PUBLIC ADMINISTRATION - GABRIELA CORINA SLUSARIUC (Annals of the University of Petrosani: Economics)
The perception of the population is that corruption is one of the main problems faced by local and national public administrations, being a widespread phenomenon in all governments. The most serious consequence of corruption is the illegal redistribution of resources in society, as some social groups win and others lose. In this paper, we study the perception of the civil society upon the problem of integrity, ethics, transparency and corruption to the level of local administration of Vulcan City, Romania. There were discussions with civil servants, with execution and management functions, with contract staff, and a questionnaire for civil society was created and used to analyze the perception of Vulcan citizens.